Bullying and associated factors in adolescents aged 11 to 15 years - Silva,Ricardo Azevedo da (2012)
INTRODUCTION: Bullying among adolescents has become the subject of extensive research due to its negative effects on attitude and behavior. However, Brazilian literature on the topic is scarce. OBJECTIVE: To assess bullying and associated factors among adolescents in a population-based sample in southern Brazil. METHOD: Population-based, cross-sectional study with adolescents aged 11 to 15 years living in the municipality of Pelotas, state of Rio Grande do Sul, Brazil. RESULTS: A total of 1,145 adolescents were included. Bullying behaviors and attitudes were found to be associated with the following factors: intentionally skipping classes, failing at school, using alcohol, smoking cigarettes, using illegal drugs, having engaged in sexual intercourse, carrying a weapon, being involved in an accident/being run over by any vehicle, and being involved in fights with physical aggression. CONCLUSION: Bullying is associated with several behaviors that pose risk to the adolescents' physical and psychological health.